Application of a vibrational impedance head to the measurement of the complex elastic modulus by the driving point impedance method - ZIÓŁKOWSKI, W.; ŚLIWIŃSKI, A. (Archives of Acoustics, 1991)
A rheological model of an impedance head is considered and the expression for its mechanical impedance Z_H has been derived. The numerical results of the modulus |Z_H| and the experimental data were compared. Also, the phase angle dependence of the measuring head Φ_num for a given rheological model and the experimental curve Φ_exp of the Brüel-Kjaer type 8001 impedance head are compared. The presented model of the measuring head impedance was used to determine the impedance for the following mechanical system: beam-measuring head-element joining the head and the sample. The experimental results of the complex modulus of elasticity against frequency for samples of a few polymers: plexiglass, PVC and Razotex B are presented as a verification of the model.